Collaborative Reading for Deeper Meaning: Literature Circle as a Strategy for Improving Student Comprehension - Lord Eljeen F Bayugo; Catlyn M Borje; Angelica C.i Domingo (Program Studi Tadris Bahasa Indonesia Institut Agama Islam Negeri Lhokseumawe, 2025)
This study determined the influence of the literature circle strategy as a teaching method to develop reading skills among 37 Grade 10 students in the Laboratory High School Department of Abra State Institute of Sciences and Technology. Using a descriptive-comparative and experimental research design, the investigation measured students’ interpreting reading ability to determine the main idea, to find the information, to infer, and to sequence before and after treatment. The descriptive method was used to determine the levels of students’ initial reading comprehension, while a comparative method was used to explore and compare the students’ reading comprehension levels at different stages of the study, and an experimental method was used to determine the effectiveness of the literature circle. It emerged that students had shown adequate understanding before the intervention, but had difficulty with sequencing. Results following the intervention were significantly improved in all comprehension features, but most notably in identifying main ideas and locating information. The pre- and post-intervention scores showed a statistically significant difference. The research concluded that the literature circle did enhance reading comprehension in all of the areas; however, it focused on the main idea, looking for information, inference, and sequencing. Suggestions were to integrate literature circle strategy into regular instruction to improve sequencing skills, support students’ varied learning styles, foster collaboration, and increase overall comprehension. Explicit instruction focused on sequencing may be integrated using visual aids and graphic organizers to help students practice and internalize sequencing skills. Further research was recommended to examine the impact of the strategy on diverse student populations for wider adoption.